Management of severe pulmonary Langerhans cell histiocytosis in children. Issue 8 (8th June 2020) - Eckstein, Olive S.; Nuchtern, Jed G.; Mallory, George B.; Guillerman, R. Paul; Musick, Matthew A.; Barclay, Mhairi; Bhatt, Jayesh M.; Davies, Patrick; Grundy, Richard G.; Martin, Alice; Hilliard, Tom; Lowis, Stephen P.; et al.
Abstract: Patients with pulmonary Langerhans cell histiocytosis (LCH) typically have a benign course but may have extensive cystic lung disease with rare life‐threatening complications including multiple and recurrent pneumothoraces and respiratory failure. We report seven severely affected pediatric patients treated with chemotherapy, aggressive chest tube management, and pleurodesis of whom five survived. Patients with extraordinary amounts of pulmonary cystic disease and multiple pneumothoraces due to LCH can have remarkable, curative outcomes with early recognition, optimal LCH‐directed therapy, and supportive care.